Empowerment of Village Health Worker to Become Assistance to Mother Groups in Prevention of ISPA in Toddlers by Using Complementary Therapy - Anwar, Lufthiani; Karota, Evi; Siregar, Cholina Trisa (Talenta Publisher, 2020)
ISPA is a respiratory disorder that causes children to tend to be lethargic, fussy, and lack of appetite, thus reducing the child's immunity which affects other health problems. The use of Complementary Therapies can help to reduce the impact of disease incidence, especially ISPA in toddlers at home as an alternative therapy for self-medication for families. It is hoped that the involvement of village health worker in the mother group in the community is directly involved in implementing the program to create and increase the ability to live healthy in a sustainable manner. The method of implementing community service activities is carried out by providing education, training and mentoring to 41 people consisting of village health worker and mother groups. The implementation of activities for the mothers group began with distributing pre-test questionnaires, then continued with providing health education about complementary therapies, herbal therapy simulations and toddler massage training to village health worker and mother groups, the activities were evaluated by providing posttest sheets. The results of the implementation of community service activities after health education and training activities obtained good knowledge about complementary therapies (75.6%) and sufficient knowledge (24.4%), paired t-test results before and after health education and the training obtained p value 0.005. It is hoped that village health worker can become activists and health promoters for mothers in an effort to prevent health problems by using complementary therapies.